The Influence of Work Motivation, Leadership Style, and Compensation on Employee Performance - Nurzaman, Nurzaman; Fadhlillah, Penny Rahmah (SAN Scientific, 2023)
This study aims to determine the effect of work motivation, leadership style, and compensation on employee performance. This research is designed as explanatory research. The research population is the employees of PT. Inti Bangun Sejahtera (IBS) helpdesk fiber optic and transmission division with a sample of 50 respondents. Data was collected using a questionnaire instrument. Data analysis using the Partial Least Square Structural Equation Modeling Method. The results of the study show that work motivation, leadership style, and compensation can be used as models that have a great fit to be used as models that can predict their effect on employee performance. Work motivation has a positive effect on employee performance; Leadership style has a positive effect on employee performance; and compensation does not affect employee performance. Companies must be able to create comfort in order to improve the performance of the company's employees